Understanding the relationship between life priorities and life satisfaction in individuals with mental disorders - Yoshioka, Daisuke; Yamanashi, Takehiko; Arima, Kazushi; Kajitani, Naofumi; Kiyama, Noriko; Sawada, Minami; Asakura, Sizuri; Miura, Akihiko; Matsuo, Ryoichi; Komatsu, Koji; Noma, Hisashi; Iwata, Masaaki (PCN reports, 2025)
Mental healthcare has recently shifted from focusing solely on treating psychiatric symptoms to enhancing patients' subjective well-being. However, research on the factors contributing to life satisfaction among individuals with mental disorders remains limited. This study investigated the life aspects that patients with schizophrenia, depression, and bipolar disorder considered important, their satisfaction with these aspects, and how these factors affect overall life satisfaction. A survey was conducted among 152 outpatients at our hospital and six other affiliated hospitals. The participants evaluated their overall life satisfaction, rated the importance of various life aspects, assessed their satisfaction with each, and identified what they considered most important in their lives. A multiple regression analysis revealed the predictors of life satisfaction. Text mining was used to analyze free-text responses. The average life satisfaction scores were comparable with those of the general Japanese population. The multiple regression analysis revealed that satisfaction with mental health, romantic relationships, and work were significant predictors of life satisfaction, unlike demographic factors such as age, sex, and diagnosis. The text mining analysis revealed that family was the most frequently mentioned life priority across all diagnostic groups. By integrating targeted interventions for improving life satisfaction with a deeper understanding of patients' fundamental values, mental healthcare can provide more comprehensive and practical support.